PENGARUH KINERJA APARATUR DESA TERHADAP PENINGKATAN PELAYANAN MASYARAKAT PADA KANTOR DESA LOMPU KECAMATAN CINA KABUPATEN BONE - Aswin, Aswin; Syam, Marniati; Jaya, Fahril (LPPM Universitas Muhammadiyah Mamuju, 2024)
This research proposes to determine the performance of village officials at the Lompu Village Office, Cina District, Bone Regency. 1). To find out about community services at the Lompu Village Office, Cina District, Bone Regency. 2). To determine the influence of the performance of village officials on services to the community at the Lompu Village Office, Cina District, Bone Regency. The type of research used in this research is quantitative. The population in this study is the entire object that is the source of data in this study, namely all people who have received services at the Lompu Village Office, Cina District, Regency. The sampling technique used, the sample that will be taken in this research is 15% of the number of people who have received services at the Lompu Village Office, Cina District, Bone Regency. So the sample for this research is 15% X 360= 54 people and 8 employees as informants . The data analysis techniques used are simple regression analysis and correlation analysis. The results of this research show that 1). The level of performance of village officials at the Lompu Village Office, Cina District, Bone Regency is classified as very high with a percentage of 66.67% 2) The level of service of village officials at the Lompu Village Office, Cina District, Bone Regency to the community is classified as high with a percentage of 50% 3). The level of performance of village officials influences services to the community at the Lompu Village Office, Cina District, Bone Regency with a coefficient interval of 0.87 or 87%, which means the level of influence is very high and the rest is influenced by other factors at 13%.